Evaluasi Pelaksanaan Pendekatan Pembelajaran Mendalam Pada TK Negeri Pembina Tais Kabupaten Seluma - Mimpira Haryono; Yuni Herlina (Journal Of Dehasen Educational Review, 2025)
This study aims to evaluate the implementation of the immersive learning approach for early childhood at Pembina Tais State Kindergarten, Seluma Regency. The immersive learning approach emphasizes active child involvement, meaningful experiences, the development of creativity, and critical thinking skills. This study used a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The results indicate that teachers have implemented the principles of immersive learning, such as guiding children's exploration, encouraging reflection, and providing meaningful learning opportunities. However, challenges remain in the variety of learning media, time constraints, and classroom management. To address these challenges, improving teacher competency through training, providing more creative learning media, effective time management, and regular monitoring are essential to improve the quality of immersive learning and ensure optimal learning experiences for children.